Electrochemical characterization of repaglinide and its determination in human plasma using liquid chromatography with dual-channel coulometric detection - Jirovský, David; Bartošová, Zuzana; Skopalová, Jana; Maier, Vítězslav (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2010)
A simple, fast and sensitive HPLC method employing dual-channel coulometric detection for the determination of repaglinide in human plasma is presented. The assay involved extraction of repaglinide by ethyl acetate and isocratic reversed-phase liquid chromatography with dual-channel coulometric detection. The mobile phase composition was 50mM disodium hydrogen phosphate/acetonitrile (60:40, v/v), pH of the mobile phase 7.5 set up with phosphoric acid. For all analyses, the first cell working potential was +380mV, the second was +750mV (vs. Pd/H(2)). Calibration curve was linear over the concentration range of 5-500nmolL(-1). Rosiglitazone was used as an internal standard. The limit of detection (LOD) was established at 2.8nmolL(-1), and the lower limit of quantification (LLOQ) at 8.5nmolL(-1). The developed method was applied to human plasma samples spiked with repaglinide at therapeutical concentrations. It was confirmed that the method is suitable for pharmacokinetic studies or therapeutic monitoring.
Keywords: elektrochemické techniky; Humans; Carbamates; Thiazolidinediones; reprodukovatelnost výsledků; karbamáty; piperidiny; Sensitivity and Specificity; Linear Models; thiazolidindiony; koncentrace vodíkových iontů; Colorimetry; Chromatography, High Pressure Liquid; Piperidines; Electrochemical Techniques; vysokoúčinná kapalinová chromatografie; hypoglykemika; lidé; senzitivita a specificita; kolorimetrie; Reproducibility of Results; lineární modely; Hypoglycemic Agents; Hydrogen-Ion Concentration